Bloques lógicos para el desarrollo de la inteligencia matemática, en los niños de Educación Inicial II, de la Escuela de Educación Básica San Felipe Neri, Ciudad Riobamba, Provincia de Chimborazo, periodo octubre 2020 - marzo 2021 - Guamán Pilco, Irma Gricelda (2021)
Logical thinking is the human being's ability to understand everything surrounding him and the relationships or differences between actions, objects, or observable facts through analysis, comparison, abstraction, and imagination. In human beings during childhood, only specific thoughts develop, so it is necessary to encourage and formulate actions to continue to evolve, without forgetting that not all children will evolve or have the ability to forge this thought in the same magnitude. Several tests are proposed to evaluate the development of mathematical, logical thinking by great scientists who are experts on the subject. However, some are developed for use in early childhood children; Therefore, this research work aims to evaluate through the Early Mathematical Assessment Test the level of mathematical knowledge and skills that the children of the San Felipe Neri School possess in order to carry out activities of counting, seriation, classification, correspondence, comparison, that exercise and highlight the child's logical level; at the same time, the activities carried out in the TEMT are focused on the use of logical blocks. The research has a Mixed approach, was qualitative and quantitative, constituted in a non-experimental design, being a descriptive and field research. In conclusion, mathematical, logical thinking is built through quantity notions, counting, series, and grouping, as evidenced in the application "Early Mathematical Assessment. These are indicators that can be verified in daily activities within the process of learning in the initial level, exercises or environments that use logic blocks that have characteristics that respond to their structure in the material, color, design, shape, or size, which contributes significantly to the apprehension of new knowledge.